Inclusive communication campaigns drive the adoption of improved seeds in Uganda - Bomuhangi, Allan; Yila, Jummai O.; Puskur, Ranjitha; Nchanji, Eileen (International Rice Research Institute, 2024)
Smallholder farmers from the Butaleja district of Eastern Uganda have long faced barriers to accessing and adopting high-quality seeds of improved varieties. Entrenched social norms, limited knowledge, and poor agricultural management practices have hindered the uptake of these high-quality seeds that could boost productivity, resilience, and livelihoods. However, a concerted effort by Work Package 6 of the Seed Equal CGIAR Initiatives is now catalyzing a paradigm shift, leveraging the power of tailored social and behavior change communication (SBCC) campaigns to reshape attitudes and practices around access to and use of quality seed. The integrated communication campaigns are part of a broader strategy to enhance sustainable change within the seed system.